Morfologia comparada dos ductos genitais femininos e gonópodos masculinos de caranguej.s Eubrachyura (Saint Laurent, 1980) - Souza, Leonardo Peres de [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Comparative works on the morphological characteristics of female genital ducts and male gonopod in crabs are scarce. Besides, little is known about the role of the genital ducts on the fertilization process or how the sperm is transferred to them, via male gonopods. The present work makes histological analyses of the female genital ducts and male gonopods on different Eubrachyura crabs families. Samples were collected on the coastline of the State of Ceará, between years 2010 and 2013. Males and females from seven different species of Eubrachyura were collected. The females were dissected and the female reproductive system was analyzed macroscopically and microscopically (light microscopy). Male gonopods were removed, fixed and processed for histological analysis and scanning electron microscopy. Anatomically, female reproductive system follows a pattern, consisting on a pair of elongated ovaries and a pair of genital ducts that extends to the exterior. The genital ducts of all species analyzed were constituted of four regions: oviduct, seminal receptacle, vagina and gonopore (vaginal opening or vulva). The ovaries can be connected to the seminal receptacle on the ventral or dorsal region. The morphohistological characteristics found on the genital ducts, mainly the vagina shape and the type of secretory epithelium of the seminal receptacle, indicates that these were related to taxon phylogeny. It was not possible to evaluate the exact fertilization site, although, the results allow inferring that the fertilization process begins at the seminal receptacle and concludes at the pleopods. We conclude that, among Eubrachyura, sperm transfer is performed by the association of the papille penile, first and second gonopods. The last two are covered in various setae types that, depending on the morphology and location, may have functions like protection, filtering, chemo and mechanoreception. Histologically, the gonopods of the analyzed...

Trabalhos comparativos das características morfológicas dos ductos genitais femininos e dos gonópodos de caranguejos são escassos. Além disso, pouco se sabe sobre a participação dos ductos genitais no processo de fertilização e ainda como se dá a transferência dos espermatozoides para estes, via gonópodos masculinos. O presente trabalho descreve morfologicamente os ductos genitais femininos e os gonópodos de diferentes famílias de caranguejos Eubrachyura. As coletas foram realizadas no litoral cearense durante os anos de 2010 a 2013. Foram coletados machos e fêmeas de sete espécies de Eubrachyura. Em laboratório, as fêmeas foram dissecadas e o sistema reprodutor feminino analisado macro e microscopicamente (microscopia de luz). Os gonópodos dos machos foram retirados, fixados e processados para análise histológica e em microscopia eletrônica de varredura. Anatomicamente o sistema reprodutor feminino segue um padrão, consistindo de um par de ovários alongados e um par de ductos genitais que se estende até o exterior. Os ductos genitais de todas as espécies analisadas são constituídos de quatro regiões: oviduto, receptáculo seminal, vagina e gonóporo (abertura genital ou vulva). Os ovários podem se ligar ao receptáculo seminal nas regiões dorsal ou ventral. As características morfohistológicas encontradas nos ductos genitais, principalmente a forma da vagina e o tipo de epitélio secretor do receptáculo seminal, indicam que estes estão relacionados com a filogenia do táxon. Não foi possível observar o real local de ocorrência da fertilização, no entanto, os resultados obtidos permitiram inferir que o processo de fertilização se inicie no receptáculo seminal e seja concluído nos pleópodos. Em Eubrachyura, a transferência dos espermatozoides é realizada por meio da associação da papila peniana, primeiro e segundo gonópodos. Os dois últimos são recobertos por diferentes tipos de setas que...
Keywords: Crustacea; Crustaceo; Morfologia (Biologia); Espermateca; Caranguejo; Caranguejo - Reprodução; Fertilização (Biologia); Caucaia (CE) - 2010-2013; Aracati (CE) - 2010-2013